Design of Citizen Fund Management Applications in Village Level Communities: Case Study: Financial Manager for Pandanaran Village Residents, Banjarnegara - Choirul Arif; Arifudin Hamzah; Himmatur Reza (Journal of Multimedia Trend and Technology, 2023)
Information technology, in general, can provide convenience for users in projecting data processing systems, in recording and recapping annual calculations as a distribution of the results of village-level fund management ("jimpitan") for each member, causing officers to experience difficulties so that the process of sharing the results of village level fund management becomes long and sometimes inaccurate calculations between the officer's recording book and the records of each individual member of the Village community. The aim of this research is to analyze the daily transaction recording system, as well as a recap of annual calculations as a guideline for distribution for village members and then design a system to make it easier to record daily transactions, as well as a recap of annual calculations of distribution for community members in Pandanaran Village, Banjarnegara. The methods that will be used in this writing are analysis methods and design methods. The results achieved from this research are to produce a cash fund management application that can assist officers in the process of recording daily transactions, as well as recapping the distribution of cash fund management proceeds for cash fund management patrol members in Pandanaran Village, Banjarnegara. So it is hoped that it can help and simplify its performance.